2003
DOI: 10.1021/ma034572q
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Behavior and Kinetic Analysis of the Chain Unfolding and Refolding and of the Concomitant Nonpolar Solvation and Desolvation of Two Elastin-like Polymers

Abstract: Water-induced chain dynamics alterations are of paramount importance in many proteinbased polymers because they determine and affect to a great extent the temperature dependence of the end properties. In this study, the thermal behavior of the reversible unfolding and refolding of poly(Val-Pro-Gly-Val-Gly) and poly(Val-Pro-Ala-Val-Gly) and of their concurrent dehydration and hydration processes has been studied by differential scanning calorimetry (DSC) and turbidimetry. Contrary to the good reversibility show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
72
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 26 publications
8
72
0
Order By: Relevance
“…For example, kinetic studies on solutions of poly(VPGVG) showed that the phase separation process is faster than the process of redissolution. This behaviour is similar to the thermal hysteresis reported for PiPAAm [78,95,102] and has been verified using temperature-modulated differential scanning calorimetry (TM-DSC) [44,78,148], a technique capable of separating phenomena that overlap thermally but present a different time response. TM-DSC uses a periodically alternating heating programme superimposed on the constant heating rate and allows differentiating between overlapping phenomena.…”
Section: Elastin-like Polymerssupporting
confidence: 76%
“…For example, kinetic studies on solutions of poly(VPGVG) showed that the phase separation process is faster than the process of redissolution. This behaviour is similar to the thermal hysteresis reported for PiPAAm [78,95,102] and has been verified using temperature-modulated differential scanning calorimetry (TM-DSC) [44,78,148], a technique capable of separating phenomena that overlap thermally but present a different time response. TM-DSC uses a periodically alternating heating programme superimposed on the constant heating rate and allows differentiating between overlapping phenomena.…”
Section: Elastin-like Polymerssupporting
confidence: 76%
“…The first examples of genetically engineered elastin-like proteins and responsive synthetic polypeptide particles and hydrogels for use in biomedicine and related fields have been successfully prepared, [106][107][108][109][110][111][112] but further developments can be expected.…”
Section: More Complex Proteinsmentioning
confidence: 99%
“…[6] ELPs reported in literature commonly comprise repeats of the pentapeptide sequence, VPG X G, where the guest residue X is varied to create ELPs with different T t . [7, 8] …”
Section: Introductionmentioning
confidence: 99%